192k views
5 votes
f(x) = 3x² + 5x – 2-g(x) = 5x³ - 4x² + 4Find (f + g)(x)O A. (f+g)(x) = -5x³ + 7x² + 5x - 6OB. (f+g)(x) = 8x³ + x + 2O C. (f+g)(x) = 5x³+3x²+x+2D. (f+g)(x) = 5x³ - x² + 5x+2

User GdZeus
by
4.6k points

1 Answer

3 votes

f(x) = 3x² + 5x – 2

g(x) = 5x³ - 4x² + 4

We want to find

(f+g)(x)

We need to add the two functions, making sure to line up the powers of x

f (x) = 3x² + 5x – 2

+g(x) = 5x³ - 4x² + 4

------------------------------

(f+g)(x) = 5x³ - x²+ 5x+2

The answer choice is choice D

D. (f+g)(x) = 5x³ - x² + 5x+2

User Askrynnikov
by
4.3k points